Budaya Kewirausahaan: Perspektif Nasional dan Organisasi dalam Ekonomi Global - Yan Endang Tri Puji Astuti; Dadang Junaedi; Yan Noviar Nasution (Universitas Veteran Bangun Nusantara, 2025)
This study conducts a systematic literature review (SLR) to explore the concept of entrepreneurial culture in the context of a rapidly evolving global economy. The primary focus of the research is to analyze the cultural factors that influence entrepreneurship at the individual, organizational, and national levels. This paper also discusses the significant role of cultural values and social norms in shaping entrepreneurial attitudes, as well as how individual motivations and intentions impact entrepreneurial success. The review identifies two interconnected concepts: National Entrepreneurial Culture (NEC) and Organizational Entrepreneurial Culture (OEC), both of which play crucial roles in creating environments that foster innovation and business development. The methodology employed in this research includes the PRISMA framework and bibliometric analysis using VOSviewer, which facilitates the mapping and identification of research trends in this field. The findings from the SLR indicate that while there has been an increase in publications on entrepreneurial culture since 2014, the topic remains relatively limited and is dominated by studies from developed countries in Europe and America. This study suggests that more attention should be given to developing countries, particularly in Asia, to fill the gaps in existing research and understand the impact of local cultures on entrepreneurship. These findings have practical implications for policymakers and educational institutions in designing policies and entrepreneurial curricula that are aligned with local cultural values and support more inclusive and sustainable entrepreneurial ecosystems.